Gender Wage Inequalities in Switzerland: the Public versus the Private Sector - Guinand, Mihaela Catalina; Tillé, Yves (My University, 2017)
Wage differences between women and men can be divided into an explained part and an unexplained part. The former encompasses differences in the observable characteristics of the members of groups, such as age, education or work experience. The latter includes the part of the difference that is not attributable to objective factors and represents an estimation of the discrimination level. We discuss the original method of Blinder (J Hum Resour 8(4):436–455, 1973) and Oaxaca (Int Econ Rev 14(3):693–709, 1973), the reweighting technique of DiNardo et al. (Econometrica 64(5):1001–1044, 1996) and our approach based on calibration. Using a Swiss dataset from 2012, we compare the estimated explained and unexplained parts of the difference in average wages in the private and public sectors obtained with the three methods. We show that for the private sector, all three methods yield similar results. For the public sector, the reweighting technique estimates a lower value of the unexplained part than the other two methods. The calibration approach and the reweighting technique allow us to estimate the explained and unexplained parts of the wage differences at points other than the mean. By using this, in this paper, the assumption that wages are more equitable in the public sector is analysed. Wage differences at different quantiles in both sectors are examined. We show that in the public sector, discrimination occurs quite uniformly both in lower and in higher-paying jobs. On the other hand, in the private sector, discrimination is greater in lower-paying jobs than in higher-paying jobs.queryPlease check and confirm the given name and family name is correctly identified for the first author and amend if necessary.
Keywords: Blinder; Oaxaca Decomposition methods Reweighting Survey sampling Wage gap